Assessment Parameters for Arrayed Pulse Wave Analysis and Application in Hypertensive Disorders. (17th February 2022) - Bi, Zi-Juan; Yao, Xing-Hua; Hu, Xiao-Juan; Yuan, Pei; Guo, Xiao-Jing; Guo, Zhi-Ling; Wang, Si-Han; Li, Jun; Shi, Yu-Lin; Li, Jia-Cai; Cui, Ji; Xu, Jia-Tuo
Abstract : Study on the objectivity of pulse diagnosis is inseparable from the instruments to obtain the pulse waves. The single-pulse diagnostic instrument is relatively mature in acquiring and analysing pulse waves, but the pulse information captured by single-pulse diagnostic instrument is limited. The sensor arrays can simulate rich sense of the doctor's fingers and catch multipoint and multiparameter array signals. How to analyse the acquired array signals is still a major problem in the objective research of pulse diagnosis. The goal of this study was to establish methods for analysing arrayed pulse waves and preliminarily apply them in hypertensive disorders. While a sensor array can be used for the real-time monitoring of twelve pulse wave channels, for each subject in this study, only the pulse wave signals of the left hand at the " guan " location were obtained. We calculated the average pulse wave (APW) per channel over a thirty-second interval. The most representative pulse wave (MRPW) and the APW were matched by their correlation coefficient (CC). The features of the MRPW and the features that corresponded to the array pulse volume (APV) parameters were identified manually. Finally, a clinical trial was conducted to detect these feature performance indicators in patients with hypertensive disorders. The independent-samples t-tests and the Mann–Whitney U -tests were performed to assess the differences in these pulse parameters between the healthy and hypertensive groups. We found that the radial passage (RP) APV h 1, APV h 3, APV h 4, APV h 3/ h 1 ( P  < 0.01), and APV h 4/ h 1 ( P  < 0.05) were significantly higher in the hypertensive group than in the healthy group; the intermediate passage (IP) APV h 4, APV h 3/ h 1 ( P  < 0.05), and APV h 4/ h 1 ( P  < 0.01) and t h e mean APV h 3, APV h 3/ h 1 ( P  < 0.05), and APV h 4/ h 1 ( P  < 0.01) were significantly higher in the hypertensive group than in the healthy group, and the ulnar passage (UP) APV h 4/ h 1 ( P  < 0.05) was clearly elevated in the hypertensive group. These results provide a preliminary validation of this novel approach for determining the APV by arrayed pulse wave analysis. In conclusion, we identified effective indicators of hypertensive vascular function. Traditional Chinese medicine (TCM) pulses comprise multidimensional information, and a sensor array could provide a better indication of TCM pulse characteristics. In this study, the validation of the arrayed pulse wave analysis demonstrates that the APV can reliably mirror TCM pulse characteristics.